TINGKAT KEPUASAN PASIEN GIGI TIRUAN SEBAGIAN LEPASAN DI RUMAH SAKIT GIGI DAN MULUT FAKULTAS KEDOKTERAN GIGI UNIVERSITAS JEMBER - Kristiana, Dewi; Naini, Amiyatun; Gunadi, Achmad (Fakultas Kedokteran Gigi Universitas Jember, 2011)
Removable partial denture is functioned as one of choice of simple treatment for partial edentulouspatients. Missing tooth can cause a lot of disorders in oral cavity. Aim of this study is to know satisfy partial edentulouspatients with variety construction of Kennedy classification in Prostodontic department dental hospital Jember university. PartiAl denture patients were examined for to know about satisfied them in dental treatment. They filled quizoner and informed consent. All of them has satisfied level toward their partial denture that they made in dentalhospital